2021
DOI: 10.2147/idr.s295798
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Diagnosis and Management of Childhood Tuberculosis

Abstract: The diagnosis of tuberculosis (TB) in children is difficult because of the low sensitivity and specificity of traditional microbiology techniques in this age group. Whereas in adults the culture of Mycobacterium tuberculosis (M. tuberculosis) , the gold standard test, detects 80% of positive cases, it only detects around 30–40% of cases in children. The new methods based on the immune response to M. tuberculosis infection could be affected by many factors. It is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 139 publications
0
13
0
3
Order By: Relevance
“…Following a meta-analysis of current data, L. H. Gutiérrez-González et al [8] concluded that the correct diagnosis of immunological changes, prognosis and the use of potential immunomodulators as adjunct therapy in TB would meet personalized treatment.…”
Section: ключові словаmentioning
confidence: 99%
“…Following a meta-analysis of current data, L. H. Gutiérrez-González et al [8] concluded that the correct diagnosis of immunological changes, prognosis and the use of potential immunomodulators as adjunct therapy in TB would meet personalized treatment.…”
Section: ключові словаmentioning
confidence: 99%
“…Alterations of specific Ig classes may potentially correlate with the extent of the disease ( 19 , 22 ). However, limited information about the humoral response in children is available ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The test has been acquainted in clinical practice with the measure of interferon gamma (IFN-γ) delivered by Mtb-contaminated platelets; lamentably, this strategy is more costly and requires a blood test to a typical leukocyte level [ 16 ], which is not generally imaginable in immunocompromised people. Accordingly, elective quantitative polymerase chain response techniques were created to recognize the safe reaction to TB contamination [ 17 ]. Be that as it may, as most quality articulation concentrates to show, the hereditary foundations can impact the particularity and affectability of the conclusion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%